Spatial Analysis of Health Services in the District of Mergasur (Raparin Journal of Humanities (RJH), 2021)
Health services are a group of preventive services that, if applied, avoid individuals contracting many diseases, including proper nutrition, comprehensive periodic medical examination, prevention of infectious diseases, safety, first aid, body care and maintenance for disabled and normal individuals, provision of prosthetic devices and tools for persons with disabilities and treatment services, and health services are considered One of the concerns that countries give a lot of their care and attention due to their great impact on caring for human health, caring for them and preserving them, and working to create their experiences and positive influence on their habits, behavior and information so that the level of their health and performance can be raised in many levels that are closely related to their health and the preservation of their bodies, It is also considered one of the important community services in the city and the district, because it provides basic medical services that the residents of this district need, and most cities, including the study area, face a number of problems and challenges, represented in the poor distribution of public services in general and health in particular, as well as their centralization Cities and non-observance of planning standards in To Distribute it in line with the population increase, urbanization, and the needs of the population from these services. Therefore, the importance of the study and its goal to study the health situation in the district of Mergasur and measure its efficiency in relation to the requirements of the population was evident through the results of the study that there is a clear lack in the volume and distribution of services provided to the population of the district in the district center Mergasur, and this lack of its existence, but also the result of the failure of the planning vision and the absence of future plans that take into account the increase in the size of the population of the district through the natural growth of the judiciary.